Effect of Stabilization Soil With Fly Ash and Bottom Ash on Characteristics of Residual Soil (Padang-Sicincin Toll Road) - Saputra, Novema Dwi; Satrya, Trihanyndio Rendy; Soemitro, Ria Asih Aryani; Hardiningsih, Sri Hastuti (Journal of Infrastructure & Facility Asset Management, 2024)
Utilization of residual soil in the Trans Sumatra Toll Road Construction Project Padang - Sicincin Section found residual soil types at Sta. 27+000 - 27 + 400 as road embankment and subgrade can be done by stabilization method where the stabilization material used is a mixture of fly ash, bottom ash, and FABA (fly ash+bottom ash). To obtain the optimum percentage of Fly ash, Bottom ash, or FABA (Fly ash Bottom ash) in improving soil behavior, the variations are 10%, 15%, and 20% of bulk density with an incubation period of 0 days, 7 days and 14 days will be selected.Based on the analysis, it is found that stabilization (fly ash, bottom ash, or FABA) results in changes in physical and mechanical residual soil properties with an increase in the CBR value in addition to fly ash at 10% with a CBR value = 4.02%, bottom ash at 20% with a CBR value = 9.49% and FABA at 20% with a CBR value = 14.32% so that the stabilized soil can be used as ordinary backfill soil or preferred backfill soil.